Bimbingan Belajar Penggunaan Konsep Laju Reaksi (Matematika) Untuk Memahami Proses Metabolisme Dalam Biologi Tingkat SMA - Hasbi, Muhammad; Fitri, Fitri (Jurnal Pengabdian Kepada Masyarakat Patikala, 2026)
The intent of this community service activity (CSA) is to improve the understanding of 12th-grade senior high school students on the concept of metabolism in biology subjects by integrating knowledge of reaction rates from mathematics or chemistry subjects. So far, students often have difficulty in interpreting changes in the speed of biological processes, such as enzyme activity or cellular respiration, which can basically be modeled and analyzed using the principle of reaction rates. This CSA activity was carried out in the form of structured tutoring (Bimbel) in senior high schools in Wajo Regency. The methods used include (1) delivery of integrated material that explains the relationship between biological variables (e.g., substrate concentration, temperature) and reaction rate variables (e.g., initial rate); (2) analysis of existing biology experimental data, where students are trained to calculate and plot reaction rate graphs from enzyme activity rate data; and (3) interactive discussions to solve problems based on applications in the context of metabolism. The evaluation results showed a significant increase in students' abilities in (1) identifying and modeling the relationship between factors that influence metabolism with reaction rate equations, (2) interpreting enzyme activity and cellular respiration graphs quantitatively, and (3) connecting enzyme reaction kinetics curves with reaction rate curves (mathematics). The positive impact of this CSA is the creation of a deeper and more holistic understanding of biology, especially metabolism, through a quantitative approach. Therefore, it is concluded that tutoring that integrates the concept of reaction rate is very effective in bridging the gap in students' understanding of high school metabolic processes. This collaborative learning model is recommended to be implemented sustainably to strengthen students' numeracy and scientific literacy.